Cystoid macular oedema after flanged intraocular lens scleral fixation using the Yamane technique: a multicentre cohort study - Hiroto Ishikawa; Kazutaka Uchida; Hiroto Terasaki; Taiji Sakamoto; Masashi Kakinoki; Masahito Ohji; Tatsuya Jujo; Hitoshi Takagi; Yoshinori Mitamura; Yutaka Yamada; Yoshihiro Takamura; Masahiko Sugimoto; et al. (Scientific Reports)
Abstract This retrospective observational multicentre cohort study compared the rate of postoperative cystoid macular oedema (CME) between two intraocular lens (IOL) scleral fixation (SFIOL) techniques: a flanged IOL fixation technique (Yamane technique) and a suture IOL transscleral fixation technique (conventional technique). The study included 207 eyes with postoperative CME that had undergone SFIOL and were observed for > 12 weeks between January 2019 and January 2021. The primary endpoint was a comparison of the rate of postoperative CME at 3 months between groups. Secondary endpoints were a comparison of postoperative best-corrected visual acuity (BCVA) at 3 months between groups and an analysis of characteristics associated with postoperative CME in the Yamane technique group. The Yamane technique group developed postoperative CME in 13.0% of eyes at 3 months, compared with 1.9% in the conventional technique group (odds ratio: 7.99, P = 0.045). Postoperative BCVA was consistently significantly higher in the Yamane technique group. Although many retinal surgeons have performed the Yamane technique because of its convenience for SFIOL, our findings suggest that the Yamane technique carries an increased risk of postoperative CME compared with the conventional suture method. Therefore, careful management of postoperative CME is needed after SFIOL.